MIND THE GAP Greenland: Is there a gap between educational goals of the government and the aspirations of young people in Narsaq? - Fridfinnsdottir, Elin Thora (UiT Norges arktiske universitet, 2014)
Mind the gap is a thesis based on fieldwork conducted in Narsaq, Greenland in July 2013 and compares the rationale behind the government’s high priority to increase educational standards of the population with the reluctance of young people in Narsaq to answer that call. Young people in Narsaq, like the population of rest of Greenland are going through a period of great changes, both environmentally and politically. This thesis examines how these changes will affect the young people in Narsaq and their educational prospects and aspirations. The findings of this study are in line with a mixture of Alan Barnard’s general hypothesis on foraging mode of thought and Merete Watt Boolsen’s social inheritance theory. Some of the findings can be explained by applying Barnard’s hypothesis on foraging mode of thought as there is still a strong sense of the traditional life style of Inuit hunter and gatherers among Greenlanders even if they now live in towns. And Merete Wall Boolsen’s theory of social inheritance helps explain how hard it is to go against your culture when it comes to education, as the parents of many young people in Narsaq lack higher education and there are few positive role models in the area who do.